The Impact of Independence, Audit Experience, Competence and Red Flags on Auditors, Fraud Detection Ability - Sahara, Ulfa; Widiastuti, Ni Putu Eka (CV. Civiliza Publishing, 2025)
This study aims to examine the influence of independence, audit experience, competence, and red flags on auditors’ ability to detect fraud. Data were collected through the distribution of questionnaires to auditors working at Public Accounting Firms across Indonesia. The respondents consisted of auditors currently employed in these firms. The findings reveal that independence, audit experience, and red flags do not have a significant impact on auditors’ ability to detect fraud. However, the study demonstrates that competence significantly influences auditors’ effectiveness in detecting fraudulent activities.